1993
DOI: 10.1016/0014-5793(93)81692-s
|View full text |Cite
|
Sign up to set email alerts
|

K+‐driven sinusoidal efflux of glutathione disulfide under oxidative stress in the perfused rat liver

Abstract: Tert-butyl hydroperoxide (BHP), hydrogen peroxide and diamide caused a rapid and simultaneous release of glutathione disulfide (GSSG) and K + in the isolated perfused rat liver. Both BHP-induced effluxes were suppressed by prior depletion of hepatic glutathione, but not by co-infusion of desferrioxamine which prevented lipid peroxidation and cell death. High K + media decreased the GSSG efflux even though hepatic GSSG levels remained high. The GSSG and K ÷ effluxes were repeatable if cellular K + recovered aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This is of interest, because oxidative stress alters the activity of several enzymes in 1-carbon metabolism, in addition to the ones directly dependent on PLP (24). Masuda et al (38) have shown that oxidative stress causes K 1 efflux from the mitochondria and that the increased K 1 gradient between the cytoplasm and the blood promotes GSSG transport by both the high-and low-affinity GSSG transporters. To simulate this effect of oxidative stress on GSSG transport, we multiplied the V max of both the high-affinity and low-affinity GSSG transporters by a factor of the form (2) (see ''Methods'').…”
Section: Resultsmentioning
confidence: 99%
“…This is of interest, because oxidative stress alters the activity of several enzymes in 1-carbon metabolism, in addition to the ones directly dependent on PLP (24). Masuda et al (38) have shown that oxidative stress causes K 1 efflux from the mitochondria and that the increased K 1 gradient between the cytoplasm and the blood promotes GSSG transport by both the high-and low-affinity GSSG transporters. To simulate this effect of oxidative stress on GSSG transport, we multiplied the V max of both the high-affinity and low-affinity GSSG transporters by a factor of the form (2) (see ''Methods'').…”
Section: Resultsmentioning
confidence: 99%
“…HdeD is also a periplasmic protein contributing to acid resistance ( 38 ). KefB is a potassium/proton antiporter that protects against electrophiles ( 39 ) and is the only protein of the tLST that specifically contributes to chlorine resistance. KefB exchanges intracellular potassium and extracellular protons, leading to acidification of the cytoplasm ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian cells, abnormal glutathione homeostasis, particularly glutathione depletion, occurs after exposure to many chemicals/ drugs and plays a role in certain degenerative diseases (e.g., Parkinson's), cell aging, and apoptosis (Nestelbacher et al, 2000;Schulz et al, 2000) (Hammond et al, 2001;Lou et al, 2003). Alternatively in hepatic cells efflux of glutathione disulfide (GSSG) constitutes the primary mechanism for turnover of the hepatic glutathione pool (Bartoli and Sies, 1978;Ookhtens et al, 1985;Masuda et al, 1993). Alternatively in hepatic cells efflux of glutathione disulfide (GSSG) constitutes the primary mechanism for turnover of the hepatic glutathione pool (Bartoli and Sies, 1978;Ookhtens et al, 1985;Masuda et al, 1993).…”
Section: Introductionmentioning
confidence: 99%